2016
DOI: 10.1007/978-3-319-41501-7_20
|View full text |Cite
|
Sign up to set email alerts
|

Human Detection Based on Infrared Images in Forestry Environments

Abstract: Abstract. It is essential to have a reliable system to detect humans in close range of forestry machines to stop cutting or carrying operations to prohibit any harm to humans. Due to the lighting conditions and high occlusion from the vegetation, human detection using RGB cameras is difficult. This paper introduces two human detection methods in forestry environments using a thermal camera; one shape-dependent and one shape-independent approach. Our segmentation algorithm estimates location of the human by ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The work in [11] presented vision based algorithms for the detection and classification of crops with images captured with a monocular camera installed in a UAV and, although not directly related to fire detection, a useful tool for the analysis of the rural environment in which air vehicles are working. Another work that collected methods of image processing with applicability in this area was presented by [12], in which, through the analysis and processing of images captured by a thermal camera, the detection of people in forest areas was carried out, which is a tool of great interest for the cooperative work between air vehicles and operational personnel on the ground.…”
Section: Related Workmentioning
confidence: 99%
“…The work in [11] presented vision based algorithms for the detection and classification of crops with images captured with a monocular camera installed in a UAV and, although not directly related to fire detection, a useful tool for the analysis of the rural environment in which air vehicles are working. Another work that collected methods of image processing with applicability in this area was presented by [12], in which, through the analysis and processing of images captured by a thermal camera, the detection of people in forest areas was carried out, which is a tool of great interest for the cooperative work between air vehicles and operational personnel on the ground.…”
Section: Related Workmentioning
confidence: 99%
“…3) (e.g. Brunner and Gizachew, 2014;Hauglin et al, 2017;Oveland et al, 2018;Wells, 2018), obstacles (Lideskog, 2018;Puliti et al, 2018), people (Ostovar et al, 2016) and what effects the machines have on the terrain (Marra et al, 2018;Melander and Ritala, 2018;Salmivaara et al, 2018). There is a huge variation in the methods used, with typical techniques including computer vision via two-dimensional (2D) and three-dimensional (3D) terrestrial laser scanners (Talbot et al, 2017).…”
Section: Knowing the Location Of Surrounding Objectsmentioning
confidence: 99%
“…Imaging sensors can be deployed on vehicles or forest machines for object detection or to assist operations. Some studies have fully demonstrated their potential for application, such as color camera systems for tree detection and distance measurement [10], stereo camera systems for scanning and reconstructing land previously processed by mounders [11], human detection in forest environments using a thermal camera [12], structured light cameras used for log recognition [13], and fusion of multiple imaging sensors to achieve more complex functions such as modeling of forest nonstructural roads [14]. The application of imaging sensors can improve the environmental observation ability of the forest machine system and is a good assistant to the visual observation of the operator in the operation cabin.…”
Section: Introductionmentioning
confidence: 99%